Renewable policy in a competitive environment: key issues. (14th January 2008) - Huber, Claus
This paper focuses on renewable policy and how the increasing number of renewable technologies can be integrated into liberalised markets for power generation and CO2 reduction options. Five key aspects regarding renewable energy sources have been identified and will be analysed: market conformity, compatibility with other policies, technological development, effectiveness and economic efficiency of the RES support and international coordination and burden sharing. No optimal support scheme exists that stimulates all RES-E technologies, neither over their entire technological lifecycle nor at the same time. Investment incentives are normally a very suitable instrument for supporting more immature technologies in the R&D phase. Once if they are more mature, i.e. technologies are already available on the market for commercial use, fixed feed-in tariffs are appropriate instruments due to their secure character. If the technology is sufficiently matured and the market is large enough to guarantee competition among the market actors, a quota obligation based on TGC or a premium feed-in tariff can be the right support tools. These instruments are with respect to adaptation to operation on the common power market. One necessary pre-condition for this step is that competition on the conventional power market exists too.